Bone marrow protection by amifostine in Re-186-HEDP treatment - Klutmann, Susanne (Radiology and oncology (Ljubljana), 2000)
Background. in the last years various reports dealt with radioprotective effects of amifostine (Ethyol, USB, Philadelphia, PA). Since amifostine is markedly accumulated in bone marrow it looks worthwhile to study the radioprotective effects of amifostine on bone marrow in patients treated with Re-186-HEDP. As a first step animal studies were performed using New Zealand White rabbits. Materials and methods. A total of 18 rabbits received 300 MBq Tc-99m-HDP for whole-body scintigraphy. Thereafter, 9 animals were treated with 200 mg/kg body weight amifostine, and 9 rabbits served as controls receiving physiological saline solution. Then, these 18 rabbits received 400 MBq Re-186-HEDP i.v. Two rabbits served as untreated controls and received neither Tc-99m-HDP nor Re-186 HEDP. Blood samples were taken at the beginning and in two-week-intervals for the duration of two months in all 20 animals. Laboratory findings were determined for white and red blood cells, for platelet count and for hemoglobin. Two months after therapy all animals were sacrificed, and both femora were removed surgically for histopathological examination of bone marrow. Results. In controls as well as in amifostine-treated animals, the red blood cell count and the hemoglobin were almost constant at all times of observation. In 9 control rabbits the mean platelet count was 265.22+-127.41 Mrd/1 prior to Re-186-HEDP-therapy. Two weeks after therapy the mean platelet count was reduced to 211.22+-52.8 Mrd/1.Prior to Re-186-HEDP-therapy the mean platelet count of amifostine-treated rabbits was not significantly different (p.0.05) from control rabbits. Two weeks after injection of the radionuclide the mean platelet count decreased to 180.67+-37.43 Mrd/1 in the amifostine group (Abstract truncated at 2000 characters.)
Keywords: amifostin; Amifostine; Bone marrow; Bone neoplasms; Disease models, animal; Erythrocyte count; Erythrocyte indices; kostni mozeg; onkologija; Platelet count; preventivna medicina; Rabbits; Radiation effects; Radiation-protective agents; radiologija; Radionuclide imaging; Rhenium; Secondary; Therapeutic use; zdravljenje